Slow depolarizing stimuli differentially activate mechanosensitive and silent C nociceptors in human and pig skin - Rukwied, Roman; Thomas, Christian; Obreja, Otilia; Werland, Fiona; Kleggetveit, Inge Petter; Jorum, Ellen; Carr, Richard; Namer, Barbara; Schmelz, Martin (Pain, 2020)
High-threshold mechanosensitive and mechanoinsensitive (“silent”) nociceptors have similar electrical thresholds for transcutaneous sine wave stimulation at 4 Hz that selectively activates cutaneous C nociceptors in human skin. Their fundamentally different functions particularly in chronic pain warrant differential stimulation protocols. We used transcutaneously delivered slow depolarizing stimuli (half-sine, 500 ms duration, 0.01-1 mA) in humans to assess intensity-response relations for the induction of pain psychophysically and recorded activation of mechanosensitive and silent nociceptors in healthy volunteers by microneurography. Differential C-fiber activation was confirmed in single-fiber recordings in pig allowing for stimulation amplitudes up to 10 mA. Perception and pain thresholds to half-sine wave pulses were 0.06 ± 0.03 mA and 0.18 ± 0.1 mA, respectively, and caused pain in an amplitude-dependent manner (n = 24). When matched for pain intensity, only sine wave stimulation induced an instant widespread axon reflex erythema (n = 10). In human microneurography, half-sine stimulation activated mechanosensitive nociceptors (n = 13), but only one of 11 silent nociceptors. In pig skin, the amplitude-dependent activation of mechanosensitive nociceptors was confirmed (0.2-1 mA, n = 28), and activation thresholds for most silent nociceptors (n = 13) were found above 10 mA. Non-nociceptive low-threshold mechanosensitive C fibers (n = 14) displayed lower activation thresholds for half-sine wave stimuli with an amplitude-dependent discharge increase between 0.01 and 0.1 mA. We conclude that transcutaneous electrical stimulation with 500-ms half-sine wave pulses between 0.2 and 1 mA causes amplitude-dependent pain by preferential activation of mechanosensitive C nociceptors.
Gesehen am 15.12.2025